A high‐quality reference genome for Fraxinus pennsylvanica for ash species restoration and research. (27th November 2021) - Huff, Matt; Seaman, Josiah; Wu, Di; Zhebentyayeva, Tetyana; Kelly, Laura J.; Faridi, Nurul; Nelson, Charles D.; Cooper, Endymion; Best, Teodora; Steiner, Kim; Koch, Jennifer; Romero Severson, Jeanne; et al.
Abstract: Green ash ( Fraxinus pennsylvanica ) is the most widely distributed ash tree in North America. Once common, it has experienced high mortality from the non‐native invasive emerald ash borer (EAB; Agrilus planipennis ). A small percentage of native green ash trees that remain healthy in long‐infested areas, termed "lingering ash, " display partial resistance to the insect, indicating that breeding and propagating populations with higher resistance to EAB may be possible. To assist in ash breeding, ecology and evolution studies, we report the first chromosome‐level assembly from the genus Fraxinus for F . pennsylvanica with over 99% of bases anchored to 23 haploid chromosomes, spanning 757 Mb in total, composed of 49.43% repetitive DNA, and containing 35, 470 high‐confidence gene models assigned to 22, 976 Asterid orthogroups. We also present results of range‐wide genetic variation studies, the identification of candidate genes for important traits including potential EAB‐resistance genes, and an investigation of comparative genome organization among Asterids based on this reference genome platform. Residual duplicated regions within the genome probably resulting from a recent whole genome duplication event in Oleaceae were visualized in relation to wild olive ( Olea europaea var. sylvestris ). We used our F . pennsylvanica chromosome assembly to construct reference‐guided assemblies of 27 previously sequenced Fraxinus taxa, including F . excelsior . Thus, we present a significant step forward in genomic resources for research and protection of Fraxinus species.